PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE HOLLYWOOD SQUARE REVIEW UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA PADA POKOK BAHASAN LARUTAN ASAM DAN BASA DI KELAS XI IPA 2 SMA NEGERI 5 PEKANBARU - Sari, Vivi; Amran, Elva Yasmi; ', Susilawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This is a classroom action research. This research is an attempt toimprove student learning activities in chemistry on class XI IPA 2 of SMAN 5Pekanbaru by using active learning strategies Hollywood Squares Review. Improvedstudent learning activity is the activity of asking questions, submit answers or opinions,group discussion and enthusiastic about the game of Hollywood Squares. The researchwas conducted with two cycles, in the first cycle consists of three meetings and thesecond cycle consists of two meetings which includes four stages of implementation,namely: planning, action, observation, and reflection. Data collection includedobservation and test. The results showed that the percentage of students increasedactivity and achieving the success criteria. The percentage of student activity in the firstcycle of 66,07% with categorized good and the second cycle of 81,65% withcategorized very good. Percentage of learning outcomes is also seen from masterylearning that enhances and have achieved success criteria. The percentage of masterylearning students in the first cycle reached 64,29%,which has not reached the criteria ofsuccess, while in the second cycle students learning completeness percentage of 80,95%has achieved succes criteria. Based on the results obtained, it can be concluded that theuse of active learning strategies types Hollywood Square Review can to increase theactivity and student learning outcomes.Keyword: Active learning strategies types Hollywood Square Review, activities, learningoutcomes